INFLUENCE OF IMPULSE MAGNETIC FIELD ON GRAPHITE MORPHOLOGY OF HIGH-ALLOY IRON - A. G. Anisovich; I. N. Rumyantseva; L. V. Bisluk; E. I. Marukovich; V. F. Bevza; V. A. Harjkov (Литьë и металлургия)
The results of researches of change of microstructure of heavily alloyed austenitic cast-iron ChN1507 subjected to magnetoimpulse processing are given. It is established that microhardness rises on all section of the sample.